Objective Measurement of Ball-Handling Proficiency in Wheelchair Sports: A Systematic Review - Altmann, Viola C.; Mason, Barry S.; Geurts, Tijmen; Camp, Sanne A. J. H. van de; Vanlandewijck, Yves C. (Frontiers in Rehabilitation Sciences, 2022)
Background In Paralympic sports, classification of athletes based on the impact of impairments on the ability to perform is needed, to prevent a one-sided and predictable outcome of the competition in which the least impaired athlete has the best chance to win. Classification is developing from expert opinion based to evidence based. In wheelchair court sports, there is evidence to support the impact of impairment on wheeled mobility, but not on ball handling. To assess the impact of impairment on the ability to perform ball-handling activities, standardised tests for ball handling are needed. Purpose To assess if reliable and valid standardised tests for the measurement of ball-handling proficiency in a wheelchair or able-bodied court sports exist; to assist in the development of Evidence-Based Classification (EBC) in wheelchair court sports according to the guidelines of the International Paralympic Committee (IPC). Methods The review was conducted according to the Meta-Analysis of Observational Studies in Epidemiology (MOOSE) statement. Search terms used were “wheelchair,” “ball,” “ball sports,” “test,” and “performance.” Databases searched were Medline, Embase, PubMed, and Sport Discus. Study quality was assessed using the Strengthening the Reporting of Observational Studies in Epidemiology checklist. Results Twenty-two articles were included. Foundational Movement Skills in ball-handling proficiency were assessed. Tests for throwing maximal distance showed sufficient reliability and validity. Precision in throwing showed low-to-moderate reliability and conflicting results in validity. Throwing techniques differed between studies. Dribbling the ball showed high reliability, but conflicting results in validity. Conclusions Tests for throwing maximal distance, throwing precision, and dribbling the ball can be used in standardised tests for activity limitation in wheelchair court sports. However, tests need to be adapted and standardised and then reassessed for reliability and validity in athletes with and without arm impairment.